Mothers' Awareness of Anorectal Malformations: A Pointer to Delayed Diagnosis in a Developing Country - Lawal, Taiwo A.; Fatiregun, Akinola A.; Yusuf, Oyindamola B. (European Journal of Pediatric Surgery, 2013)
Introduction Delay in the presentation of babies with anorectal malformations (ARMs) to the pediatric surgeon accounts for a major cause of morbidity and mortality in developing countries. In countries lacking proper guidelines for screening and newborn physical examination, a lot of responsibility is placed on parents and caregivers; with mothers often being the first to note abnormalities in their babies. The aim of the study was to assess the awareness of mothers about ARM and their knowledge about normal or abnormal appearance of the anus.Materials and Methods A descriptive cross-sectional study involving mothers attending immunization clinics at two hospitals in a developing country was conducted using a structured interviewer administered questionnaire. Data were obtained on sociodemographic characteristics, awareness of ARM, and knowledge of appearance of the anus by requesting mothers to identify if three pictures of the perineum were normal or abnormal.Results A total of 365 mothers participated in the study with age ranging from 17 to 42 years. Only 71 (19.5%) mothers had ever heard about ARM. A picture of a girl with ARM and rectoperineal fistula was correctly identified by 66 (18.1%) and that of a boy with ARM and rectoperineal fistula by 71 (19.5%) mothers. A higher proportion (25.0%) of the mothers who were older than 30 years were aware of ARM than those younger than 30 years (16.0%), (p = 0.035). Participants with tertiary education were more likely to be aware of ARM than those with 12th grade or less education (31.1 vs. 6.9%, p < 0.001). Skilled workers were also more likely to be aware of ARM than unskilled workers and artisans (41.1 vs. 8.1%, p < 0.001). The predominant technique of “checking” the anus by the mothers was “inspection of their baby's perineum.”Conclusion Level of awareness of ARMs was low among women interviewed. Educational intervention targeting young mothers from low socioeconomic class is suggested.
Keywords: anorectal malformations; awareness; mothers